1990
DOI: 10.1002/ajmg.1320360402
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of ring 14 chromosome from mother to two sons

Abstract: We report on a family with transmission of a ring chromosome 14 from an affected mother to her 2 sons. The mother was mosaic, 46,XX,r(14)/45,XX,t(14q21q). Both of her sons, affected by seizures and mental retardation, have the karyotype 46,XY,r(14). In considering the association of translocation 14:21 in the mother with ring 14, we postulate that either the ring chromosome was formed first and then opened with translocation of the partially deleted chromosome 14 to chromosome 21, or the 14:21 translocation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Our literature review identified several cases with characteristics in common with the four cases reported here. 4,8,10,11,13 Data are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review identified several cases with characteristics in common with the four cases reported here. 4,8,10,11,13 Data are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
“…Miller-Dieker syndrome should be suspected in an infant with lissencephaly, refractory epilepsy, and severe developmental delay. Funduscopy revealing retinal abnormalities could suggest ring chromosome 14 (138)(139)(140). Characteristic facial features, gait, and absence of speech with a predominance of myoclonic, atonic, and atypical absence seizures and a classic age-related EEG pattern are the hallmarks of Angelman syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures are universal in this condition (134). At least 35 cases were reported (135-137), some of which are familial (138)(139)(140). Any potential epilepsy genes would most likely be sited in the terminal long arm region, because the terminal short arm contains no single-copy genes.…”
Section: Ring Chromosome 14mentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether it is also a common disorder in other ring chromosomes, we reviewed epilepsy frequencies in a total of 403 cases with ring chromosomes including 22 autosomes and X chromosome (Fig. 3) [Palka et al, 1986;Fagan et al, 1988;MacDermot et al, 1990;Matalon et al, 1990;Freyberger et al, 1991;Calabrese et al, 1994;Migliori et al, 1994;Lurie, 1995;Flejter et al, 1996;Lanzi et al, 1996;Wahlstrom et al, 1996;Conte et al, 1997;Cutenese et al, 2000;Rodriguez et al, 2000;Tonk et al, 2000;Barajas-Barajas et al, 2001;Dee et al, 2001;Stankiewicz et al, 2001;He et al, 2002;Muroya et al, 2002;Urban et al, 2002;van Karnebeek et al, 2002;Concolino et al, 2003;Ishmael et al, 2003;Morimoto et al, 2003;Parmar et al, 2003;Shashi et al, 2003;Battini et al, 2004;Bedoyan et al, 2004;Le Caignec et al, 2004;Leppig et al, 2004;Rope et al, 2004;Tumer et al, 2004;Zhang et al, 2004;Alkuraya et al, 2005;Nishiwaki et al, 2005]. Only ring chromosomes 14, 17, and 20 are strongly associated with seizure disorders.…”
Section: Seizure Disorder and Ring Chromosomementioning
confidence: 99%